Los convenios de asociación con entidades sin ánimo de lucro: falencias en su aplicación y perspectivas hacia la eficiencia de la inversión social (2020)
The shortcomings in the application of the legal figure of the partnership agreements under the regulations of decrees 777 and 1403 of 1992, evidenced through the theoretical-practical analysis, showed a negative impact on the application of the agreements. It evidenced the need for a new regulation that, in a real and effective way, will harmonize this typology with the General Statute of Public Procurement and the application of the principles that govern it, especially those of transparency and objective selection, unknown and violated in a repeated way with the improper and exaggerated use of this exceptive figure, in order to obviate the selection of mechanisms contemplated in the contractual law. Despite the promulgation of Decree 092 of 2017 enshrined the application of the principles of state contracting to partnership agreements with non-profit entities, it did not determine objective criteria that would guarantee the objective selection of the non-profit organizations (NPO) and, much less, its effective integration into the contractual statute. The problematic question of this manuscript is: how to overcome the shortcomings in the application of partnership agreements to ensure the efficiency in social investment of public resources? The specific objectives of the article are to determine the historical and normative antecedents of the partnership agreements; demonstrate the flaws in the application of the legal figure evidenced in the study of five disciplinary partnership agreements, in light of decrees 777 and 1403 of 1992, and propose the inclusion of the partnership agreements as a modality of state contracting to guarantee the application of the principles of transparency and objective selection.